Evidence of antagonism in vitro and in vivo of extracts from Banisteriopsis laevifolia (A. Juss) B. Gates against the rice blast fungus - Simão, Jorge Luiz Souza; Teodorico, Matheus Santos de Souza; Silva, Maria Ivanir de Sousa Cardoso; Coelho, Carla Thaís Pereira; Bezerra, Gustavo de Andrade; Arriel Elias, Marina Teixeira; de Fillipi, Marta Cristina Corsi; de Araújo, Leila Garcês; Pasqualotto Severino, Vanessa Gisele (Frontiers in Natural Products, 2023)
Rice blast is a common disease caused by Magnaporthe oryzae which affects rice production worldwide, including Brazil. To reduce the use of harmful pesticides, sustainable control options are necessary for managing rice blast. One possible option is to use plant extracts because they produce secondary metabolites capable of inhibiting the pathogen and controlling the disease. This study aimed to evaluate the potential of ethanolic extracts of leaves and flowers from Banisteriopsis laevifollia, a native Brazilian plant, to antagonise M. oryzae. In vitro antifungal activity assays were carried out, in which mycelium growth reduction, conidia germination, and appressorium formation of M. oryzae were evaluated. In addition, in vivo assay for suppression of leaf blast severity by extracts was done. We also explored the identification of secondary metabolites from ethanolic extracts of leaves and flowers by HPLC–HRMS. Results showed that both leaf and flower extracts inhibited mycelial growth in 21.72% and 30.49%, respectively, due to the inhibition of ergosterol production. Additionally, both extracts inhibited melanin production in the mycelium of M. oryzae by inhibiting tyrosine production. Both leaf and flower extracts significantly inhibited conidia germination and appressorium formation. Furthermore, rice leaves treated with the extracts suppressed by 18.17% and 18.97% leaf blast severity, with the 1.00 mg/mL concentration of flower extract and 0.75 mg/mL concentration of leaf extract, respectively, showing the most significant reduction of leaf blast. The extracts contain phenolic compounds, including 2,3,7,8-tetrahydroxy-chromeno-(5,4,3)-chromene-5,10-dione, 3-(4-hydroxyphenyl)-2-propenoic acid, 2-(3,4-dihydroxyphenyl)-3,4-dihydro-1(2H)-benzopyran-3,5,7-triol, 3,4′,5,7-tetrahydroxyflavone, 3′,4′,5,7-tetrahydroxyflavone, 4′,5,7-trihydroxyflavanone, 3,3′,4′,5,7-pentahydroxyflavone, 3,3′,4′,5,7-pentahydroxyflavone -3-O-glucoside, and 3,3′,4′,5,7-pentahydroxyflavone-3-O-rutinoside, which are likely responsible for the antifungal activity of the extracts. Overall, this study demonstrates the potential of plant extracts as a sustainable alternative for the management of rice blast.